2019
DOI: 10.1016/j.coviro.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Crimean-Congo hemorrhagic fever and expansion from endemic regions

Abstract: Crimean-Congo hemorrhagic fever (CCHF) is a virus-mediated hemorrhagic disease that occurs over a wide geographic region. In recent years, a variety of active and passive surveillance networks have improved our knowledge of areas with existing circulation of Crimean-Congo hemorrhagic fever virus (CCHFV), the etiologic agent of CCHF. These investigations aid in better defining the distribution of the virus. Expansion of a virus into new areas can occur through a variety of means, including introduction of infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 77 publications
1
92
0
3
Order By: Relevance
“…Saksida et al [9], Hasanoğlu et al [7] and Yilmaz et al [10] reported the mortality rate associated with CCHF to be 27.5%, 8.1%, and 5%, respectively. The mortality rate was reported to be lower in countries such as Turkey and Russia, where CCHF is endemic, but the underlying reasons have not yet been elucidated [5,6]. In agreement with findings in the literature, the mortality rate was found to be 8.1% in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Saksida et al [9], Hasanoğlu et al [7] and Yilmaz et al [10] reported the mortality rate associated with CCHF to be 27.5%, 8.1%, and 5%, respectively. The mortality rate was reported to be lower in countries such as Turkey and Russia, where CCHF is endemic, but the underlying reasons have not yet been elucidated [5,6]. In agreement with findings in the literature, the mortality rate was found to be 8.1% in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…The mortality rate associated with this disease is 5%-30%; however, the mortality rate is lower in endemic regions such as Turkey and Russia. It remains unclear whether the differences in mortality are related to regional differences or case management strategies [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Fatality rates range from ~5% to −80% in different countries. A relatively low fatality rate (4.6%) has been reported from the most recent Turkish series compared to reports from other countries 1 . CCHF causes both disease‐related morbidity and mortality and economic losses with the increase in the number of cases reported in the world.…”
Section: Introductionmentioning
confidence: 84%
“…In particular, the climate change along with anthropogenic factors may have caused significant effect on reproduction rate of Hyalomma tick. This inevitably resulted in extensive amplification of virus through tick vertebra tick cycle (along with increase of wildlife population) [20,[43][44][45] . Owing to security reasons, several activities including, agriculture, farming, and hunting were limited in the rural areas in Tokat and neighbouring provinces between 1995 and 2001.…”
Section: Emergence Of Crimean Congo Haemorrhagic Fever Disease In Turkeymentioning
confidence: 99%
“…This is particularly important to map areas where outbreaks could occur in future and to alert public health systems. If the prevalence of CCHFV increases in ticks, in conjunction with virus specific antibody circulation in wild and domestic animals in any given area, cases of disease outbreak may occur [9,44,45] . These examples highlight the importance of veterinary medicine in the one health initiative, particularly in case of CCHFV disease.…”
Section: One Health Initiative To Combat Cchf Diseasementioning
confidence: 99%